The given equation -2(11 - 12x) = -4(1 - 6x) has infinite solutions
<u><em>Solution:</em></u>
Given that we have to solve the given expression
Given expression is:
-2(11 - 12x) = -4(1- 6x)
We have to use distributive property to solve the given expression
The distributive property lets you multiply a sum by multiplying each addend separately and then add the products.
Which means,
a(b + c) = ab + ac
Apply this in given expression
-2(11 - 12x) = -4(1-6x)
-22 + 24x = -4 + 24x
When both sides of the equation are simplified, the coefficients are the same, then infinite number of solutions occur
If we end up with the same term on both sides of the equal sign, such as 24x = 24x, then we have infinite solutions
Answer:
C
140
Step-by-step explanation:
Answer:
49
Step-by-step explanation:
You would add 4+5+6+7+8+9+10 to get the sum of 49.
Are you crazy, that’s way to much. Sorry buddy you’re by you’re self but at least Brainly thinks I’m answering a question.LOL.Sucks to be you
Answer: Ix - 950°C I ≤ 250°.
Step-by-step explanation:
Ok, the limits are:
700°C to 1200°C.
The first step is to find the mean these numbers:
M = (700°C + 1200°C)/2 = 950°C
Now let's find the distance between the mean and the limits (which is equal to half the difference between our numbers)
D = (1200°C - 700°C)/2 = 250°C.
Now we can write our relation as:
Ix - MI ≤ D
Ix - 950°C I ≤ 250°.
if x = 1200°C.
I1200°C - 950°CI = 250°C ≤ 250°C ---- true.
if x = 700°C
I700°C - 950°CI = I-250°CI = 250°C ≤ 250°C ---- true